ID: 237. Issue 1 (November 2015) - Borst, Katharina; Frenz, Theresa; Spanier, Julia; Tegtmeyer, Pia-Katharina; Chhatbar, Chintan; Namineni, Sukumar; Lienenklaus, Stefan; Köster, Mario; Heikenwälder, Mathias; Sutter, Gerd; Kalinke, Ulrich
<x xml:space="preserve">Abstract</x> Most viruses developed mechanisms that inhibit the induction or the function of type I interferon (IFN-I). Vaccinia virus (VACV), a large DNA-encoded poxvirus, encodes several IFN-I evasins, including the viral IFN-I receptor B18. Nevertheless, here we found that VACV infection still induced local IFN-I responses in secondary lymphoid organs, which are mainly sensed within the liver. VACV infected IFN-I receptor deficient (IFNAR−/−) mice developed fulminant disease, associated with high virus loads in organs such as liver and spleen, imbalanced cytokine responses within the blood, and eventually succumbed to infection. Elevated ALT/AST levels in the serum of VACV infected IFNAR−/− mice supported the hypothesis that IFNAR triggering of the liver played a major role in the antiviral response. Histological analysis of livers of VACV infected IFNAR−/− mice revealed a severe acute hepatitis, massive infiltration of immune cells, and acute tissue apoptosis in the absence of IFNAR-signaling. Interestingly, VACV infected mice with a hepatocyte selective IFNAR ablation (Alb-CreIFNARflox/flox) showed moderate hepatitis as observed in wild-type mice, whereas mice with a cell type-specific IFNAR deletion only in myeloid cells (LysM-CreIFNARflox/flox) showed enhanced hepatitis. Thus, local IFN-I responses sensed by myeloid cells prevented immunopathology within the liver, presumably due to the induction of myeloid derived suppressor cells (MDSC). Collectively these results indicate that although the induction of serum IFN-I is sequestered, VACV infection induces local IFN-I responses that play a central role in modulating immune responses and thus in reducing immunopathology and hepatitis.